2016
DOI: 10.5688/ajpe80349
|View full text |Cite
|
Sign up to set email alerts
|

A Team-Based Practicum Bringing Together Students Across Educational Institutions and Health Professions

Abstract: Objective. To assess student perceptions of teamwork during an interprofessional exercise and to evaluate if students could identify domestic violence through a standardized patient interview. Design. Medical, pharmacy, nursing, physical therapy, and social work students were assigned to teams to interview and examine a patient with a "cut on the hand" later revealed a result of domestic violence. They also practiced suturing technique and developed a patient care plan. A postexercise survey was administered. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…In 10 studies (19%), simulation was used to assess generalist competencies (Bogo et al, 2013, 2012, 2011; Carrillo & Thyer, 1994; Katz et al, 2014; Lu et al, 2011; Petracchi, 1999; Petracchi & Collins, 2006; Rawlings, 2012; Tufford et al, 2017). The remaining 12 studies used simulation to assess specialized competencies, including suicide risk assessment (Bogo, Regehr, Baird, Paterson, & LeBlanc, 2017; Regehr et al, 2016), social work practice with LGBQQ populations (Logie et al, 2015), depression (Gellis & Kim, 2017), child neglect (Tufford et al, 2015), practice with children and families (Scourfield et al, 2019), screening of suicide and violence (Sampson et al, 2018), risk assessment in child welfare (LeBlanc et al, 2012), domestic violence in health care (MacDonnell et al, 2016), child maltreatment (Regehr et al, 2010), substance use (Sacco et al, 2017), and children’s services (Wilkins et al, 2018). The OSCE was used in 10 of 22 studies (45%; e.g., Bogo et al, 2012; Gellis & Kim, 2017; Katz et al, 2014; Lu et al, 2011; Sampson et al, 2018; Scourfield et al, 2019; Tufford et al, 2015, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 10 studies (19%), simulation was used to assess generalist competencies (Bogo et al, 2013, 2012, 2011; Carrillo & Thyer, 1994; Katz et al, 2014; Lu et al, 2011; Petracchi, 1999; Petracchi & Collins, 2006; Rawlings, 2012; Tufford et al, 2017). The remaining 12 studies used simulation to assess specialized competencies, including suicide risk assessment (Bogo, Regehr, Baird, Paterson, & LeBlanc, 2017; Regehr et al, 2016), social work practice with LGBQQ populations (Logie et al, 2015), depression (Gellis & Kim, 2017), child neglect (Tufford et al, 2015), practice with children and families (Scourfield et al, 2019), screening of suicide and violence (Sampson et al, 2018), risk assessment in child welfare (LeBlanc et al, 2012), domestic violence in health care (MacDonnell et al, 2016), child maltreatment (Regehr et al, 2010), substance use (Sacco et al, 2017), and children’s services (Wilkins et al, 2018). The OSCE was used in 10 of 22 studies (45%; e.g., Bogo et al, 2012; Gellis & Kim, 2017; Katz et al, 2014; Lu et al, 2011; Sampson et al, 2018; Scourfield et al, 2019; Tufford et al, 2015, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Engaging in simulated client interviews can teach students about procedural competencies, such as knowledge and skills, and meta-competencies, such as self-awareness, emotion regulation, and decision-making (Bogo et al, 2013, 2014; Kourgiantakis, Bogo, & Sewell, 2019). Studies have found that simulation is an effective method for teaching generalist competencies in social work practice (Katz, Tufford, Bogo, & Regehr, 2014; Kourgiantakis, Bogo, & Sewell, 2019; Kourgiantakis, Sewell, Bogo, 2019), as well as specialized competencies across sectors such as child welfare (Pecukonis et al, 2016), mental health (Gellis & Kim, 2017; Kourgiantakis, Sewell, Bogo, 2019), health care (Kuehn, Huehn, & Smalling, 2017), domestic violence (MacDonnell, George, Nimmagadda, Brown, & Gremel, 2016), addictions (Sacco et al, 2017), and family therapy (Mooradian, 2007).…”
Section: Simulation-based Learningmentioning
confidence: 99%
“…Given these trends, and a pre-existing robust collaboration that already exists across health professional schools in Rhode Island, including health professional schools at the Warren Alpert Medical School of Brown University (AMS), the University of Rhode Island (College of Nursing and College of Pharmacy), and Rhode Island College (RIC; School of Social Work and School of Nursing), 9,10 an opportunity was identified to focus on interprofessional SBIRT education and implementation. In 2015, these health professional schools were awarded a Medical Professional Training grant from the Substance Abuse and Mental Health Services Administration (SAMHSA), a branch of the U.S. Department of Health and Human Services (grant number H79 TI025938).…”
Section: Settingmentioning
confidence: 99%
“…Therefore, development of appropriate curriculum to train capable and competent nurses with required skills, knowledge, and attitudes to promote health is of crucial importance. [ 4 ] Curriculum is a scientific area that, at least, includes four components of objectives, content, methodologies, and assessment method. The existence of a comprehensive curriculum consistent with the needs of health system constitutes the main basis in training human resources required by the health system.…”
Section: Introductionmentioning
confidence: 99%